2021
DOI: 10.1038/s41380-021-01061-w
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine for mood disorders: objective assessment, risk prediction, pharmacogenomics, and repurposed drugs

Abstract: Mood disorders (depression, bipolar disorders) are prevalent and disabling. They are also highly co-morbid with other psychiatric disorders. Currently there are no objective measures, such as blood tests, used in clinical practice, and available treatments do not work in everybody. The development of blood tests, as well as matching of patients with existing and new treatments, in a precise, personalized and preventive fashion, would make a significant difference at an individual and societal level. Early pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 37 publications
(89 reference statements)
0
54
0
Order By: Relevance
“…In addition, several studies have identified the genes encoding the serotonin transporter (SLC6A4) [116,117], IL-1β [118][119][120], and FK506 binding protein 5 (FKBP5 or FKBP-51) [116,121] as potential genetic biomarkers for depression. The genetic loci related to depression (e.g., SNPs in LHPP, SIRT1 region) have also been revealed although there are differences between studies [24,26].…”
Section: Molecular Diagnosis Of Depression: An Epigenetic Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several studies have identified the genes encoding the serotonin transporter (SLC6A4) [116,117], IL-1β [118][119][120], and FK506 binding protein 5 (FKBP5 or FKBP-51) [116,121] as potential genetic biomarkers for depression. The genetic loci related to depression (e.g., SNPs in LHPP, SIRT1 region) have also been revealed although there are differences between studies [24,26].…”
Section: Molecular Diagnosis Of Depression: An Epigenetic Perspectivementioning
confidence: 99%
“…The genetic loci related to depression (e.g., SNPs in LHPP, SIRT1 region) have also been revealed although there are differences between studies [24,26]. Furthermore, there are attempts to identify blood gene expression biomarkers and provide predictive information as well as precise and personalized diagnosis and treatment for depression [117,122]. Recently, researchers have attempted to integrate functional neuroimaging and genetic data (neuroimaging genetics) for depression.…”
Section: Molecular Diagnosis Of Depression: An Epigenetic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bioinformatics enrichment of groups of converged genes leads to insights into pathways and mechanisms that may be involved in different phenotypes [ 74 ]. This methodology has been successfully utilized, even with limited size cohorts and datasets, in the study of gene associations with chronic fatigue syndrome [ 50 ]; biomarker identification for suicidality [ 48 ], attention-deficit–hyperactivity disorder [ 49 ], stress-related psychiatric disorders [ 75 ], and mood disorders [ 52 ]; and the discovery of novel candidate genes and signaling pathways for epileptogenesis [ 47 ] and retinol or retinoic acid exposure [ 51 ]. In order to understand the underlying biological processes and mechanisms mediating the effects of Cr administration, we performed a CFG analysis on differentially expressed genes in humans and mice for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…While human data increase the clinical relevance (specificity), animal model data increase the ability to identify the signal (sensitivity). Combined together, we enhance our ability to distinguish signals from noise, even with limited cohorts and datasets [ 46 ]; therefore, CFG is useful for identifying novel candidate genes and pathways for specific phenotypes [ 47 , 48 , 49 , 50 ] and compound-mediated gene regulation [ 51 , 52 ]. It is necessary to point out the complementary features of low- and high-throughput analysis, given that subsequent validation of the identified metabolic hubs requires the high sensitivity, lower noise, and reproducibility of low-throughput techniques (e.g., post-transcriptional regulation assessment, targeted-molecules expression, protein–protein interactions) [ 53 ].…”
Section: Introductionmentioning
confidence: 99%